Wideband spectrum sensing using step-sampling based on the multi-path nyquist folding receiver - Tian, Kai-lun; Jiang, Kai-li; Cao, Sen; Gao, Jian; Xiong, Ying; Tang, Bin; Zhang, Xu-ying; Li, Yan-fei (Defence technology, 2024)
Wideband spectrum sensing with a high-speed analog-digital converter (ADC) presents a challenge for practical systems. The Nyquist folding receiver (NYFR) is a promising scheme for achieving cost-effective real-time spectrum sensing, which is subject to the complexity of processing the modulated outputs. In this case, a multipath NYFR architecture with a step-sampling rate for the different paths is proposed. The different numbers of digital channels for each path are designed based on the Chinese remainder theorem (CRT). Then, the detectable frequency range is divided into multiple frequency grids, and the Nyquist zone (NZ) of the input can be obtained by sensing these grids. Thus, high-precision parameter estimation is performed by utilizing the NYFR characteristics. Compared with the existing methods, the scheme proposed in this paper overcomes the challenge of NZ estimation, information damage, many computations, low accuracy, and high false alarm probability. Comparative simulation experiments verify the effectiveness of the proposed architecture in this paper.